2023
DOI: 10.1002/adom.202302095
|View full text |Cite
|
Sign up to set email alerts
|

The Faraday Effect and Phase Transition in the CH3NH3PbI3 Halide Perovskite Single Crystal

Anastasia A. Shumitskaya,
Vadim O. Kozlov,
Nikita. I. Selivanov
et al.

Abstract: The spin degree of freedom of charge carriers in halide‐perovskite semiconductors can be highly useful for information photonics applications. The Faraday effect is known to be the best indicator of paramagnetism of the material and of the spin‐light interaction. In this work, the Faraday effect is demonstrated, for the first time, in a hybrid organic–inorganic halide perovskite MAPbI3 (MA+ = CH3NH). The Faraday rotation and birefringence are measured across the tetragonal‐cubic phase transition at 327 K. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, the long carrier lifetimes and low nonradiative recombination rates were taken advantage of when demonstrating optically pumped laser emission in MAPbI 3 nanowires . The first studies on spin relaxation and decoherence in HP have been performed in MAPbI 3 films , and revisited later. This opened the field to other studies on spin dynamics in HP materials , and has revealed interesting effects and differences with more conventional semiconductors …”
Section: Introductionmentioning
confidence: 99%
“…For example, the long carrier lifetimes and low nonradiative recombination rates were taken advantage of when demonstrating optically pumped laser emission in MAPbI 3 nanowires . The first studies on spin relaxation and decoherence in HP have been performed in MAPbI 3 films , and revisited later. This opened the field to other studies on spin dynamics in HP materials , and has revealed interesting effects and differences with more conventional semiconductors …”
Section: Introductionmentioning
confidence: 99%